A sala de aula universitária como espaço de inovação: investigando o curso de nutrição da Unisinos - Pedroso, Maísa Beltrame (Universidade do Vale do Rio do Sinos, 2006)
This work is based on the pedagogical practices that are considered significant by the students of the Nutrition Course at the Universidade do Vale do Rio dos Sinos – UNISINOS and the advocacy of the lecturers that developed these practices. It was sought to discover whether these experiences signified innovation in the sense of a paradigmatic break, understanding innovation as a discontinuous process, of ruptures with the traditional forms of teaching and learning. Within this goal, it was also sought to understand how the lecturers, seen as innovators by their students, constructed the route to follow as educators, identifying the processes instituted in their pedagogical practice. A qualitative methodology and the principles of an ethnographic approach were used in the expectation of understanding the processes in the social context under which they were produced, on the basis of their history and the contingencies of their production. To carry out the research thirty nine students and four lecturers from
Keywords: aprendizagem significativa; curso de Nutrição; inovação pedagógica; pedagogia universitária; saberes docentes; educator knowledge; innovation pedagogy; meaningful learning; Nutrition course; university pedagogy; Ciências Humanas